COMBILE-T intervention: An effort to control the motivation to behave in a consumptive manner of Pay Later in Gen Z - Laily Rahmah; Anisa Nisfi Zakia; Dzulfikar Maula Al Farizi; Muhammad Imadudin Al Rasyid; Lailil Muna Sahara (Proyeksi, 2026)
This study aims to assess the effectiveness of the COMBILE-T intervention in controlling consumer motivation in Gen Z, triggered by easy access to Pay Later services. This study uses a mixed methods sequential explanatory approach. The first stage was conducted using a quantitative experimental method using a pretest-posttest control group design. The second stage was conducted using a qualitative approach through interviews to explain and deepen the results of the quantitative research. Qualitative data were analyzed using thematic analysis. A total of 16 students from a private university in Semarang who met the inclusion criteria were selected through a purposive sampling technique and randomly divided into an experimental group  and a control group ), each consisting of 8 participants. Data collection instruments were a consumer behavior scale (α = 0.802) and interviews. Quantitative data analysis was conducted using the Wilcoxon Signed-Rank test to measure differences within groups, and the Mann–Whitney U test to compare between groups. The results showed that the EG consumer score decreased by an average of 3.63 points, while the CG increased by 1.75 points. The difference in change between the experimental (EG) and control (CG) groups was statistically significant (p = 0.030; p<0.05). Although the decrease in EG scores was not statistically significant (p = 0.128; p>0.05), qualitative results revealed eight themes of positive change, including increased self-control, financial attitudes and literacy, rational decision-making skills, financial management, emotional well-being, self-awareness, and motivation to become an agent of social change. These findings suggest that the Combile-T intervention] is potentially effective in reducing consumer behavior, as indicated by the significant difference in change between the experimental and control groups. The Combile-T intervention demonstrated a significant differential effect compared to the control group in suppressing increased consumer behavior among Gen Z pay-later users.